Music and the Queer Body in English Literature at the Fin de Siècle - Riddell, Fraser (Humanities, 2022)
Synthesizing music, literature and theory, Fraser Riddell reveals the importance of music in emergent queer identities at the fin de siècle. Illuminating for both students and researchers of the period, his compelling arguments for music's queer agency will fascinate anyone interested in Aestheticism, Decadence and the Bloomsbury Group.